Effect of different surfaces on plasma stripping of photoresist - Chanana R.K.; Dwivedi R.; Srivastava S.K. (My University, 2025)
The effect of different surfaces on plasma ashing is studied. For this purpose three different surfaces are considered-silicon, SiO2 and metallized aluminium. Photoresist is spun, exposed and developed on these surfaces and plasma ashing is performed. The ashing time with respect to spinner speed and flow rate of O2 is determined. The results reveal that the ashing time of the resist is dependent on the background layer on which the resist is coated. © 1991.